Conflict, collusion and corruption in small-scale gold mining: Chinese miners and the state in Ghana. Issue 4 (2nd October 2017) - Crawford, Gordon; Botchwey, Gabriel
ABSTRACT: As gold prices soared from 2008 onwards, tens of thousands of foreign miners, especially from China, entered the small-scale mining sector in Ghana, despite it being 'reserved for Ghanaian citizens' by law. A free-for-all ensued in which Ghanaian and Chinese miners engaged in both contestation and collaboration over access to gold, a situation described as 'out of control' and a 'culture of impunity'. Where was the state? This paper addresses the question of how and why pervasive and illicit foreign involvement occurred without earlier state intervention. Findings indicate that the state was not absent. Foreign miners operated with impunity precisely because they were protected by those in authority, that is, public officials, politicians and chiefs, in return for private payments. Explaining why state institutions failed in their responsibilities leads to reflection about the contemporary state in Ghana. It is concluded that the informality and corruption characteristic of neopatrimonialism remains predominant over legal–rational structures, albeit in a form that has adapted to neoliberal restructuring. Public office remains a means of private enrichment rather than public service. Such findings cast a shadow over the state and government in Ghana, and tarnish its celebration as a model of democratic governance for Africa.